Valsartan Mitigates the Progression of Methotrexate-Induced Acute Kidney Injury in Rats via the Attenuation of Renal Inflammation and Oxidative Stress - Kutbi D; Almalki RS (Dove Medical Press, 2024)
Dina Kutbi,1,2 Riyadh S Almalki3 1Department of Pharmacy, King Fahad Armed Forces Hospital, Jeddah, Saudi Arabia; 2Department of Pharmacology, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 3Department of Pharmacology and Toxicology, Faculty of Pharmacy, Umm AL-Qura University, Makkah, Saudi ArabiaCorrespondence: Dina Kutbi, Department of Pharmacy, King Fahad Armed Forces Hospital, Jeddah, Saudi Arabia, Email dina.t.kutbi@gmail.comBackground: Methotrexate (MTX) is a folic acid antagonist, commonly administered for the treatment of a variety of cancers. However, methotrexate toxicity including bone marrow suppression and hepatic and renal toxicity limits its use. Angiotensin AT1 receptor blockers including Valsartan (Val) possess the ability to ameliorate MTX-induced toxicity through various mechanisms. In this study, we explored the potential reno-protective effects of Val against MTX-induced acute kidney injury in rats.Methods: Twenty-four Wistar rats were randomly segregated into 3 groups. Group 1 served as the control group and received an oral dose of 1mL/kg of normal saline. Group 2 received a single dose of 20 mg/kg of MTX intraperitoneally (IP) for 5 days. Group 3 received a single IP dose of 20 mg/kg of MTX followed by an oral dose of 10 mg/kg of Valsartan for 5 days. At the end of the experiment, the levels of serum kidney biomarkers, inflammatory and oxidative stress markers were accessed. Furthermore, the effect of MTX on kidney tissue histology was examined.Results and discussion: Our results showed that MTX treatment increased the level of serum kidney and inflammatory biomarkers and decreased the level of antioxidants SOD and GSH while increasing the lipid peroxidation contents. Furthermore, MTX treatment caused structural changes to kidney histology. However, the administration of Val significantly prevented these changes.Conclusion: Valsartan possesses nephroprotective potential and might serve as a potential therapeutic strategy against MTX-induced kidney injury.Keywords: acute kidney injury, inflammation, methotrexate, oxidative stress, renal toxicity, renoprotection